2022
DOI: 10.1055/a-1755-4925
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Repair for ACL Injury: A Meta‑analysis of Randomized Controlled Trials

Abstract: We aim to compare the curative effect of primary repair for anterior cruciate ligament (ACL) injury with reconstruction and provide the reliable evidence for its clinical application. The literatures were searched in PubMed, EMBASE, Springer, and other medical literature databases published between January 1970 and June 2021. Basic characteristics, surgery technique, clinical outcome scores and physical examination results were recorded and evaluated. Seven randomized controlled trials (RCT) were eligible for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Finally, the clinical tools used could have some influence on our results. However, the KT1000 is the most used device to measure ATT [ 66 ], and the reliability of Microfet, the device used to measure isometric strength, is >0.95 [ 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the clinical tools used could have some influence on our results. However, the KT1000 is the most used device to measure ATT [ 66 ], and the reliability of Microfet, the device used to measure isometric strength, is >0.95 [ 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…48 The second reason is the prevalence of arthroscopic surgery, which is less invasive and leads to higher postoperative activity function level, lower reoperation rates, and earlier start of rehabilitation than open arthrotomy. 29 Another important reason for the revisitation of primary repair is the invention of new surgical techniques to enhance the biomechanical properties of the repaired ACL (SAR, suture augmentation repair, DIS, IBLA, and BEAR).…”
Section: The Orthopaedic Journal Of Sports Medicinementioning
confidence: 99%
“…Recent studies have reported varying findings regarding the outcomes of arthroscopic ACL repair compared with ACL reconstruction, with some studies indicating similar outcomes and others suggesting better or worse results in terms of mixed objective and patient-reported outcomes. 1,21,27,29,39,50,53 It is widely acknowledged in the academic community that this variability in outcomes may be attributed to the insufficient duration of follow-up. 24,39,46,49 In recent meta-analyses, most of the included studies had ≤2 years of follow-up, and almost no study reached 5 years of follow-up.…”
mentioning
confidence: 99%
“…In the 1970s and 1980s, open primary ACL repair was commonly performed but was eventually abandoned due to poor surgical results and complications (Feagin and Curl, 1976;Taylor et al, 2009). With the development and application of arthroscopy, biotechnology, stronger internal fixation techniques, and more rational postoperative rehabilitation, ACL repair has received renewed attention from orthopedic surgeons (van der List and DiFelice, 2017; DiFelice and van der List, 2018; Mahapatra et al, 2018;Ahmad et al, 2019;Hoogeslag et al, 2019;Murray et al, 2020;Li, 2022). Isolated ACL repair has been reported using various techniques including suture anchor primary ACL repair, internal brace ligament augmentation, bridge-enhanced ACL repair (BEAR), and dynamic intraligamentary stabilization (DIS) methods (Heusdens, 2021).…”
Section: Introductionmentioning
confidence: 99%